An Integrated Analysis of Network Pharmacology and Experimental Validation to Reveal the Mechanism of Chinese Medicine Formula Naotaifang in Treating Cerebral Ischemia-Reperfusion Injury - Yang T; Chen X; Mei Z; Liu X; Feng Z; Liao J; Deng Y; Ge J (Dove Medical Press, 2021)
Tong Yang,1 Xiangyu Chen,1 Zhigang Mei,1,2 Xiaolu Liu,2 Zhitao Feng,2 Jun Liao,1 Yihui Deng,1 Jinwen Ge1 1Key Laboratory of Hunan Province for Integrated Traditional Chinese and Western Medicine on Prevention and Treatment of Cardio-Cerebral Diseases, College of Integrated Traditional Chinese and Western Medicine, Hunan University of Chinese Medicine, Changsha, Hunan, People's Republic of China; 2Third-Grade Pharmacological Laboratory on Chinese Medicine Approved by State Administration of Traditional Chinese Medicine, Medical College of China Three Gorges University, Yichang, Hubei, People's Republic of ChinaCorrespondence: Zhigang Mei; Jinwen GeCollege of Integrated Traditional Chinese and Western Medicine, Hunan University of Chinese Medicine, NO. 300, Xueshi Road, Yuelu District, Changsha, Hunan, 410218, People's Republic of ChinaEmail meizhigang@hnucm.edu.cn; 001267@hnucm.edu.cnBackground: Cerebral ischemia-reperfusion injury (CIRI) is a crucial factor leading to a poor prognosis for ischemic stroke patients. As a novel Chinese medicine formula, Naotaifang (NTF) was proven to exhibit a neuroprotective effect against ischemic stroke, clinically, and to alleviate CIRI in animals. However, the mechanisms underlying the beneficial effect have not been fully elucidated.Methods: In this study, we combined a network pharmacology approach and an in vivo experiment to explore the specific effects and underlying mechanisms of NTF in the treatment of ischemia-reperfusion injury. A research strategy based on network pharmacology, combining target prediction, network construction, gene ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis, and molecular docking was used to predict the targets of NTF in treating the ischemic stroke and CIRI. On the other hand, we used HPLC and HRMS to identify biologically active components of NTF. Middle cerebral artery occlusion models in rats were utilized to evaluate the effect and the underlying mechanisms of NTF against CIRI after ischemic stroke.Results: Network pharmacology analysis revealed 43 potential targets and 14 signaling pathways for the treatment of NTF against CIRI after ischemic stroke. Functional enrichment analysis showed that a STAT3/PI3K/AKT signaling pathway serves as the target for in vivo experimental study validation. The results of animal experiments showed that NTF significantly alleviated CIRI by decreasing neurological score, infarct volume, numbers of apoptotic neuronal cells, increasing density of dendritic spines and survival of neurons. Furthermore, NTF could increase the expression of p-STAT3, PI3K, p-AKT. In addition, the detection of apoptosis-related factors showed that the NTF could raise the expression of Bcl-2 and reduce the expression of Bax.Conclusion: This network pharmacological and experimental study indicated that NTF, as a therapeutic candidate for the management of CIRI following ischemic stroke, may exert a protective effect through the STAT3/PI3K/AKT signaling pathway.Keywords: cerebral ischemia-reperfusion injury, stroke, network pharmacology, molecular docking, STAT3/PI3K/AKT signaling pathway